Red Hat Certified Engineer (RHCE) exam cram video workshop - Vugt, Sander van (LiveLessons (Indianapolis, Ind.), 2015)
More than 4 hours of video training detailing common exam traps, pitfalls, and difficulties on the RHCE exam. The author also walks you through a complete practice exam in real-time, so you can experience what it’s like to take the test before you ever walk into the testing facility. Red Hat Certified Engineer (RHCE) Exam Prep Workshop contains more than 4 hours of deep-dive training on common RHCE exam traps, pitfalls, and difficulties. Sander van Vugt, an experienced Red Hat instructor, trainer, and author will detail the most common mistakes people make when taking the RHCE exam, so you can avoid them in the testing facility. You will then walk through a live practice exam with the author in real-time, so you can experience first-hand what it’s like to take the test.